The association between lower socioeconomic position and functional limitations is partially mediated by obesity in older adults with symptomatic knee osteoarthritis: Findings from the English Longitudinal Study of Ageing - Witkam, Rozemarijn; Verstappen, Suzanne M. M.; Gwinnutt, James M.; Cook, Michael J.; O'Neill, Terence W.; Cooper, Rachel; Humphreys, Jennifer (Frontiers in Public Health, 2022)
Objective To assess the longitudinal associations of socioeconomic position (SEP) with functional limitations and knee joint replacement surgery (JRS) in people with symptomatic knee osteoarthritis (OA), and whether body mass index (BMI) mediated these relationships. Methods Data came from the English Longitudinal Study of Ageing, a national longitudinal panel study of adults aged ≥50 years. A total of 1,499 participants (62.3% female; mean age 66.5 (standard deviation (SD) 9.4) years; 47.4% obese) self-reporting an OA diagnosis and knee pain, with at least one BMI measurement were included. Mixed effect models estimated longitudinal associations of each SEP variable (education, occupation, income, wealth and deprivation index) and obesity (BMI ≥30.0 kg/m2) with repeated measures of functional limitations. Cox regression analyses estimated associations between SEP indicators and obesity at baseline and risk of knee JRS at follow-up. Structural equation modeling estimated any mediating effects of BMI on these relationships. Results Lower SEP and obesity at baseline were associated with increased odds of functional limitations in people with knee OA [e.g., difficulty walking 100 yards: no qualification vs. degree adjOR 4.33 (95% CI 2.20, 8.55) and obesity vs. no obesity adjOR 3.06 (95% CI 2.14, 4.37); similar associations were found for the other SEP indicators]. A small proportion of the association between lower SEP and functional limitations could be explained by BMI (6.2–12.5%). Those with lower income, lower wealth and higher deprivation were less likely to have knee JRS [e.g., adjHR most vs. least deprived 0.37 (95% CI 0.19, 0.73)]; however, no clear association was found for education and occupation. Obesity was associated with increased hazards of having knee JRS [adjHR 1.87 (95% CI 1.32, 2.66)]. As the direction of the associations for SEP and obesity with knee JRS were in opposite directions, no mediation analyses were performed. Conclusions Lower SEP was associated with increased odds of functional limitations but lower hazards of knee JRS among people with knee OA, potentially indicating underutilization of JRS in those with lower SEP. Obesity partially mediated the relationship between lower SEP and increased odds of functional limitations, suggesting adiposity as a potential interventional target.